EFEKTIVITAS PENERAPAN KARTU NIKAH DI ERA DIGITAL DI KANTOR URUSAN AGAMA KECAMATAN LOWOKWARU KOTA MALANG - Aisyahturradiah Aisyahturradiah; Ibnu Jazari; Ach Faishol (Jurnal Hikmatina, 2022)
This research is motivated by the presence of marriage cards in the digital era which has begun to be applied in various Religious Affairs Offices (KUA) throughout Indonesia, especially in KUA Lowokwaru District. The Ministry of Religion has decided to stop issuing physical marriage cards as of August 2021, instead the Ministry of Religion has launched digital marriage cards. Writing this article using field research methods, this article attempts to explain the application of marriage cards in the digital era, the effectiveness of marriage cards and the factors supporting and inhibiting marriage cards in KUA Lowokwaru District. Marriage card is a marriage registration document in the form of a card. The newlywed couple will receive an online marriage card sent by the KUA to the bride and groom via a WhatsApp number or email address. The results can be found that the effectiveness of the application of marriage cards in the digital era at the KUA, Lowokwaru District, Malang City is declared successful and runs effectively and smoothly. Keywords: Effectiveness, Marriage Card, Application